SEBARAN RUMAH TRADISIONAL DI KECAMATAN PAUH KOTA PADANG DALAM ASPEK KAJIAN GEOGRAFI BUDAYA - Hary Febrianto; Annisa; Desi Eka Putri; Fatma Azahra; Rezi Triputra Candra (PT. Jurnal Center Indonesia Publisher, 2025)
Traditional Minangkabau traditional houses are also called Rumah Gadang. Rumah Gadang is a traditional house located in West Sumatra, Indonesia. This traditional house is used by the community as a residence for the Minangkabau people or tribe. Rumah Gadang resembles a ship. Rumah Gadang is also called the traditional bagonjong house (barter house) because it has a roof that has a tall, towering roof, like buffalo horns. In general, every form of traditional house has its own meaning or story, and the Gadang traditional house is no exception. Not only do they have oval roofs, it turns out that traditional Minang Kabau houses, especially those in the city of Padang, have a cart roof in the form of a gable roof. This house is called Rumah Gadang Kajang Padati. This research aims to find out the distribution of traditional houses/old/ancient house types in the Pauh sub-district, Padang City. This research uses observation and literature study methods. This research shows the distribution of traditional houses/old/ancient house types spread across the Pauh sub-district, Padang City. In this research we can also find out the types of traditional houses spread across the Pauh sub-district, Padang City.